Mastcellens funktion vid försvar mot infektioner - Sundell Johnestedt, Jonna (2011)
The complexity of the mast cell is becoming more prominent. From being the cell recognized just to contribute to allergic inflammation it is now also associated with wound healing, protection against tumor growth and in recognition and defense against a wide range of pathogens. The location of the mast cell in the barrier between the external and internal environment of the body enables the cell to quickly respond to invading bacteria, virus and parasites. Diarrhea due to Escherichia coli infection, listeriosis, toxoplasmosis, Newcastle disease and bovine respiratory syncytial virus are examples of mast cell activating diseases that can affect animals in, as well as outside, the agricultural sector. Additionally, ticks and tick-borne diseases are of concern. Infections and their consequences are an economical loss for farmers as well as an issue for animal welfare. Therefore it is important to understand how mast cell recognize and hinder pathogens, which the mast cell does in many different ways. Also, good knowledge about the mast cell makes it possible to use its characteristics as a model for medical treatment of diseases.